Hydrogen Sulfide Inhibits Enzymatic Browning of Fresh-Cut Chinese Water Chestnuts - Dou, Yuan; Chang, Chunmei; Wang, Jing; Cai, Zhipeng; Zhang, Wei; Du, Huaying; Gan, Zengyu; Wan, Chunpeng; Chen, Jinyin; Zhu, Liqin (Frontiers in Nutrition, 2021)
This work investigates the role of hydrogen sulfide (H2S) in the browning and regulating the antioxidant defensive system in fresh-cut Chinese water chestnuts. The samples were fumigated with 0, 10, 15 μl L-1 H2S and stored at 10 °C for 8 d. The results indicated that H2S treatment prominently inhibited the browning of fresh-cut Chinese water chestnuts, reduced superoxide anion (O2•−) production rate and H2O2 content accumulation, promoted the increase of total phenol content, enhanced activities of catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) (P < 0.05). While phenylalanine ammonialyase (PAL), polyphenol oxidase (PPO) and peroxidase (POD) activities were also remained at a low level in H2S treatment (P < 0.05). This result suggested that H2S treatment might be a promising approach to inhibit browning and prolong the shelf life by enhancing oxidation resistance and inhibiting browning enzyme activity of fresh-cut Chinese water chestnuts during storage. Among them, 15 μl L-1 H2S treatment had the best effect on fresh-cut Chinese water chestnuts.